2014
DOI: 10.1123/jcsp.2014-0032
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Specialization in Professional Baseball Players

Abstract: Two developmental pathways to sport excellence have been described: early specialization and early sampling (Côté, Lidor, & Hackfort, 2009). Despite a common assumption that early specialization (defined as playing one sport exclusively and intensely before age 12) is a necessary precursor to success at the collegiate or professional levels, research to support this assumption remains unclear. To add to this literature, the current study was a survey of 708 minor league professional baseball players on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 18 publications
1
24
1
1
Order By: Relevance
“…Brooks et al reported that most adolescent athletes view specialization as beneficial for improving sport performance (91%) or making a college team (67%), similar to the large majority of parents in our study who indicated similar beliefs [8]. Similarly, in a survey of 201 youth sport parents, Padaki et al reported that 57% of parents hoped for their child to play either collegiately or professionally, and half of all parents reported that they had encouraged their child to specialize in a single sport [18]. To our knowledge, this is the first study to examine the perceived benefits of specialization among parents of adolescent baseball athletes.…”
Section: Discussionsupporting
confidence: 84%
“…Brooks et al reported that most adolescent athletes view specialization as beneficial for improving sport performance (91%) or making a college team (67%), similar to the large majority of parents in our study who indicated similar beliefs [8]. Similarly, in a survey of 201 youth sport parents, Padaki et al reported that 57% of parents hoped for their child to play either collegiately or professionally, and half of all parents reported that they had encouraged their child to specialize in a single sport [18]. To our knowledge, this is the first study to examine the perceived benefits of specialization among parents of adolescent baseball athletes.…”
Section: Discussionsupporting
confidence: 84%
“…The author did not evaluate injury incidence in the study group or report the age at which the players specialized. 13 Ginsburg et al 11 reported that 25% of professional players specialized before age 12 and the mean age of specialization was 15; again, injury rates were not discussed. In contrast, our study demonstrated that 49% of players specialized in baseball prior to high school.…”
Section: Discussionmentioning
confidence: 99%
“…Early specialization among children has become commonplace, with concepts such as Deliberate Practice and the "10,000 h rule" entering the public consciousness and strongly influencing how skills in youth are developed by coaches, teachers, and parents [3,[10][11][12]. However, this early specialization movement is not without its detractors [24,31,39], as several studies suggest that elite performance can occur with much shorter time investment than 10,000 h [2,16,33,34] and late specialization may actually produce better performances in more physiological-based sports (versus skill-based sports) than early specialization [14,30].…”
Section: Introductionmentioning
confidence: 99%